计算:4除以(根号11减去根号7),得出的值

360U3279373520 |浏览845次
收藏|2021/12/31 12:42

满意回答

2021/12/31 12:59

解4÷(√11-√7)=[4(√11+√7)]÷[(√11-√7)(√11+√7)]=[4(√11+√7)]÷[(√11)²-(√7)²]=[4(√11+√7)]÷(11-7)=[4(√11+√7)]÷(11-7)=√11+√7

尧山__1957_08

其他回答(8)
  • 4÷(√11-√7)=4(√11+√7)/(√11-√7)(√11+√7)=4(√11+√7)/4=√11+√7
    回答于 2021/12/31 15:21
  • 4÷(√11-√7)=4×(√11-√7)÷[(√11-√7)×(√11-√7)]=4×(√11-√7)÷[(√11)² -(√7)²]=4×(√11-√7)÷[11 - 7]=4×(√11-√7)÷ 4=√11+√7
    回答于 2021/12/31 15:14
  • 4÷﹙√11-√7﹚=4×﹙√11+√7﹚÷[﹙√11-√7﹚﹙√11+√7﹚]=4×﹙√11+√7﹚÷[11-7]=4×﹙√11+√7﹚÷4=√11+√7
    回答于 2021/12/31 14:50
  • 4÷(√11-√7)=4/(√11-√7)=4(√11+√7)/[(√11-√7)(√11+√7)]=4(√11+√7)/(11-7)=4(√11+√7)/4=√11+√7=3.3166247903553998491149327366707......+2.6457513110645905905016157536393......=5.9623761014199904396165484903099......
    回答于 2021/12/31 14:28
  • 4÷(√11-√7)(11-7)÷(√11-√7)=(√11+√7)(√11-√7)÷(√11-√7)=√11+√7
    回答于 2021/12/31 14:19
  • 4÷(√11-√7)=4(√11+√7)/[(√11+√7)(√11-√7)]=4(√11+√7)/[(√11)²-(√7)²]=4(√11+√7)/(11-7)=4(√11+√7)/4=√11+√7
    回答于 2021/12/31 13:54
  • 4÷(√11-√7)=4×(√11+√7)/[(√11-√7)(√11+√7)]=4×(√11+√7)/(11-7)=√11+√7
    回答于 2021/12/31 13:32
  • 4÷(√11-√7)=4/(√11-√7)=[4×(√11+√7)]÷[(√11-√7)×(√11-√7)]=[4×(√11+√7)]÷4=√11+√7
    回答于 2021/12/31 13:13
0人关注该问题
+1

 加载中...